Academic Library Sessions: Experiences and Challenges of Nazarbayev University Library - Zvonareva, Darya; Yap, Joseph M. (7th International Conference on Emerging Global Trends in University Library Development (Library Connect 2018), 2018)
The Reference Department of the Nazarbayev University Library is responsible for the development and delivery of library sessions and workshops. These are offered as part of the educational process and partnership in supporting curricular and research needs as well as to enhance the lifelong learning experience of our library users. The following categories of sessions are provided: library orientation, instruction sessions, information sessions and publishers/partners sessions. These sessions will ultimately become part of the structured information literacy program of the library. The paper seeks to describe, evaluate and assess the library sessions and workshops conducted in 2017. The paper also defines the challenges faced by librarians in conducting the sessions. Another objective is to identify improvements for raising effectiveness in organizing and delivering the library sessions.
Keywords: Nazarbayev University Library; user education; library instruction; information literacy